Research on Internal Flow Uniformity of U-Flow Pattern and Z-Flow Pattern SOFC Stacks Based on Numerical Analysis - Hao Yuan Yin; Kun-Woo Yi; Young-Jin Kim; Hyeon-Jin Kim; Kyong-Sik Yun; Ji-Haeng Yu (Energies)
This study analyzes flow uniformity in U-flow pattern and Z-flow pattern solid oxide fuel cell (SOFC) stacks, assessing their performance under different stack heights and rates of fuel/air usage. Both configurations achieved satisfactory flow distribution uniformity in the anode region at the 1 kWe scale, especially with the Z-flow design demonstrating enhanced stability. However, as stack height increased, particularly at 3 kWe, flow uniformity decreased significantly. In the cathode flow region, uniformity was highly sensitive to changes in air utilization rate, with lower air utilization causing more pronounced reductions in flow uniformity for both stack types. Increasing the height of the stack tends to reduce flow uniformity, whereas higher reactant utilization promotes more uniformity. Moreover, flow uniformity strongly correlates with the pressure drop ratio in the core area, where a higher ratio indicates better uniformity. At 75% fuel utilization, the anode flow region of the U-flow pattern 3 kWe stack exhibited excessively high local fuel utilization in the unit cell with the lowest mass flow rate, implying a risk of fuel depletion due to insufficient supply at that height. Overall, the Z-flow pattern stack showed better performance in the anode flow region, particularly at higher capacities, while the U-flow pattern stack performed slightly better in the cathode flow region under low air utilization conditions. These findings indicate that the Z-flow pattern stack is better suited for high-power applications.